AB0246 Predictive Value of a Multi-Biomarker Disease Activity Score for Successful Dose Reduction of TNF Inhibitors in Rheumatoid Arthritis: Results of the Dress Study. (9th June 2015) - Bouman, C.; van der Maas, A.; van Herwaarden, N.; Segurado, O.G.; Sasso, E.H.; van den Hoogen, F.; den Broeder, A.
Abstract : Background: Dose reduction or stopping of TNF inhibitors (TNFi) appears to be feasible and safe in patients with rheumatoid arthritis (RA), but may lead to flaring. No factors, including DAS28-CRP, have been found to predict successful dose reduction thus far 1 . The multi-biomarker disease activity (MBDA) score measures disease activity in RA on a scale of 1–100. Objectives: To investigate the predictive value of the MBDA score for clinical outcomes assessed 18 months after initial tapering of TNFi: chance of successful dose reduction or stopping, risk of flaring and risk of radiographic progression. Methods: The DRESS (Dose REduction Strategies of Subcutaneous TNFi) study is an 18-month randomised trial that investigated non-inferiority of a dose reduction strategy of adalimumab or etanercept compared with usual care. TNFi dosing was reduced every 3 months until clinical flare (DAS28-CRP increase >1.2 or >0.6 if current DAS28 ≥3.2) or stopping. In case of flare, TNFi was restarted or escalated. Major flare was defined as lasting >3 months. Data and serum were collected every 3 months and at flare visits. X-rays of hands and feet were scored using mSvdH. MBDA scores at BL, 9 and 18 months and change (Δ) from BL to 9 months were evaluated. Receiver operating characteristic (ROC) and optimal cut-off MBDA scores evaluated the predictive value of BL MBDA score for: successful dose reduction or stopping at 18 months, occurrence of any clinical flares or major flares, and incidence of radiographic progression (ΔmSvdH >0.5 over 18 months). Results: Serum and outcomes were available for 171 of 180 patients. Mean DAS28-CRP at BL was 2.2 (SD 0.7); MBDA score 33.6 (SD 12.3). At 18 months, successful stopping was possible in 19% (95% CI 12-26) of patients, dose reduction in 44% (95% CI 35-54) and no dose reduction in 37% (95% CI 28-45) (Figure 1 ). Incidence of major flare for the whole study group was 12% (20 of 171 patients). ROC analyses for prediction of successful stopping, dose reduction, major flare and any flare by MBDA score showed non-significant AUROCs. AUROC for major flare by BL MBDA score was significant only in the usual care group (0.72, 95% CI 0.56-0.88) and not the dose reduction group. ΔMBDA score from BL to 9 months was not predictive for successful stopping, dose reduction, or occurrence of (major) flare. Radiographic progression occurred in 26% of 167 patients with available data and was not predicted by MBDA score. Conclusions: In this TNFi dose reduction study, neither BL MBDA score nor ΔMBDA score from BL to 9 months was predictive for successful dose reduction or stopping; occurrence of (major) flare; or radiographic progression. Of note, BL MBDA score was predictive for flare in patients who received usual care. An explanation could be lack of variation in baseline disease activity with low disease activity in the majority of patients. Confirmation of these results is needed in other tapering studies. References: Van Herwaarden et al. Randomised controlled non-inferiority study of disease activity guided dose reduction and withdrawal of adalimumab and etanercept compared to usual care in rheumatoid arthritis. Submitted. Disclosure of Interest: C. Bouman: None declared, A. van der Maas: None declared, N. van Herwaarden: None declared, O. Segurado Shareholder of: Myriad Genetics, Inc, Employee of: Crescendo Bioscience, a wholly owned subsidiary of Myriad Genetics, Inc., E. Sasso Shareholder of: Myriad Genetics, Inc, Employee of: Crescendo Bioscience, a wholly owned subsidiary of Myriad Genetics, Inc., F. van den Hoogen: None declared, A. den Broeder: None declared